Deteksi Dini dan Promosi Kesehatan Pada Lansia dalam Pengendalian Komplikasi Penyakit Tidak Menular (PTM) di Kelurahan Barusari Kota Semarang - Ainnur Rahmanti; Syurrahmi Syurrahmi; Lu’Luah Feby Purwanti (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Non-Communicable Diseases (NCDs) such as hypertension, diabetes mellitus and heart disease are the main causes of morbidity and mortality in the elderly (elderly). The elderly need early detection and health promotion to reduce the risk of NCD complications and improve quality of life. This activity aims to increase awareness and understanding of elderly people in Barusari Village regarding the importance of early detection and control of NCDs, as well as providing health education through community-based health promotion. Implementation Method: Free Health Check: Carry out a health check to detect early signs of NCDs, such as measuring blood pressure, blood sugar levels, and checking cholesterol. Community-Based Health Promotion: Holding a health promotion campaign involving community leaders, elderly families, and health workers to create an environment that supports a healthy lifestyle for the elderly. Results: Increased public awareness about the importance of early detection and prevention of NCD complications. Elderly people who take part in health checks gain knowledge about their health conditions and are given referrals to health facilities if necessary. Conclusion: This activity was successful in increasing elderly participation in early detection and health promotion, as well as forming a community that is more concerned about controlling NCDs in the elderly group.